Царевна-лягушка и другие сказки - Билибин Иван Яковлевич (Сказки Ученого Кота, 2013)
Экземпляры: ф16 (20170914) / Инвентарный номер: 54502 / Цена: 20.00 / Сис.шифр: Д / Авт.знак: Ц 18 / ГРНТИ: 17.82.93 / ББК: 84(0)